PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMUNIKASI DAN DAMPAKNYA PADA KINERJA PEGAWAI BADAN PENDAPATAN DAERAH (BAPENDA) KABUPATEN MOJOKERTO - Subendi, Antor; Hadiyati, Ernani; Suswati, Endang (Arthavidya Jurnal Ilmiah Ekonomi, 2021)
The purpose of this study was to examine the effect of transformational leadership style and communication onemployee performance, examine the effect of transformational leadership style on communication, andcommunication strengthens the effect of transformational leadership style on employee performance. Thepopulation of this study were 45 employees of the Bapenda Mojokerto Regency so that all of them were taken assamples or used total sampling technique. Methods of data collection using survey techniques anddocumentation. The data analysis of this research used descriptive data analysis technique of percentage andPartial Least Square (PLS). The results showed that there was a significant positive effect of transformationalleadership style and communication partially on employee performance. There is a significant positive effect oftransformational leadership style on employee communication. Communication does not strengthen theinfluence of transformational leadership style on employee performance, meaning that communication cannotmediate the effect of transformational leadership on employee performance.